EFISIENSI INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) PELAPISAN LOGAM PTDI DALAM MENURUNKAN KADAR CROM (CR6+) - Tati Ruhmawati; Tatang Roni S (Poltekkes Kemenkes Bandung, 2013)
Levels of pollutants produced by PT DI after passing through wastewater are generally below the quality standard including chromium, but there are some parameters that exceed the standard quality including COD parameter. Although the levels of hexavalent chromium (Cr6+) below the quality standard, but should get attention, because of its accumulative can endanger the environment and health.The purpose of the study was to determine the efficiency of Waste Water Treatment Plant (WWTP) metal plating PT Dirgantara Indonesia (DI) in lowering levels of hexavalent chrome (Cr6+) and COD. The study was quasi-experimental with one group pretest-posttest design. Population is wastewater generated from metal plating process of PT DI, the sample is part of waste water taken from the influents, chemical processing, and effluent. Sampling method is using grab sampling method (immediate sample), with sampling techniques for physical and chemical examination. Data processing was performed using SPSS soft ware. Data analysis using Paired samples T-test and one way anova. At the influent concentration value is the same temperature of 25 0C, pH 12.7 to 13.8. Levels of hexavalent chromium (Cr6+) ranged between 1.03 mg/l to 2.10 mg/l. While the COD level ranged from 4336.64 mg/l to 4898.88 mg/l. In the process of temperature levels ranging from 25.5 0C to 26 0C, pH levels ranging from 4 to 5. While the COD level ranged from 3259.20 mg/l to 3900.00 mg/l. At the same effluent concentration value temperature of 25 0C, pH levels ranging from 7.1 to 7.3. Levels of hexavalent chromium (Cr6+) ranged between 0.01 mg/l to 0.40 mg/l. While the COD level ranged from 2400.00 mg/l to 3656.48 mg/l. After passing through the WWTP, the percentage decrease in levels of hexavalent chromium (Cr6+) ranged from 72.73% to 99.04% with an average decrease of 89.77%. Thus WWTP PT DI is efficient in reducing the levels of hexavalent chromium (Cr6+). Percentage reduction in COD level ranged from 16.91% to 44.66% with an average decrease of 30.62%. Thus WWTP PT DI has not been efficient in reducing the COD level. No difference between the levels of hexavalent chromium (Cr6+) and COD in the influent and effluent. For hexavalent chromium (Cr6+) 0.002 p value less than 0.05, for the COD level of 0.003 p value less than 0.05. There was no significant difference between concentration and effluent COD in the process, with a p value of 0,056 is greater than 0,05